2018
DOI: 10.3390/jmmp2010013
|View full text |Cite
|
Sign up to set email alerts
|

The Prediction of Surface Error Characteristics in the Peripheral Milling of Thin-Walled Structures

Abstract: Lightweight design is gaining in importance throughout the engineering sector, and with it, workpieces are becoming increasingly complex. Particularly, thin-walled parts require highly accurate and efficient machining strategies. Such low-rigidity structures usually undergo significant deformations during peripheral milling operations, thus suffering surface errors and a violation of tolerance specifications. This article introduces a general approach to mitigating surface errors during the peripheral milling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…To improve the precision of machined parts, the evaluation of surface error characteristics in thin-walled constructs during peripheral milling has been studied by Wimmer and Zaeh [1]. The process parameter optimization of thin-wall machining for wire arc additive manufactured parts is investigated by Grossi et al [2] to decrease the deformation error in the thin-walled manufactured components.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the precision of machined parts, the evaluation of surface error characteristics in thin-walled constructs during peripheral milling has been studied by Wimmer and Zaeh [1]. The process parameter optimization of thin-wall machining for wire arc additive manufactured parts is investigated by Grossi et al [2] to decrease the deformation error in the thin-walled manufactured components.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the thin wall deflections from predictions considering mechanical/thermal loads [9,10] or real-time online measurement [8,11,12], are mostly used as position-dependent feedback to reselect and design processing parameters (e.g. smart tool paths [13][14][15] or constant contact forces [16]).…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that VSR improved the shape and size of material stability to a significant level by relieving induced residual stresses in thin-walled parts. In addition to static and dynamic models, there are also analytical models related to the development of new methods for predicting the behavior of systems based on frequency response and deformations resulting from cutting forces [31].…”
mentioning
confidence: 99%